Hemodynamic Consequences of Malignant Ascites in Epithelial Ovarian Cancer Surgery*: A Prospective Substudy of a Randomized Controlled Trial. Issue 49 (December 2015) - Hunsicker, Oliver; Fotopoulou, Christina; Pietzner, Klaus; Koch, Mandy; Krannich, Alexander; Sehouli, Jalid; Spies, Claudia; Feldheiser, Aarne
Abstract : Abstract: Malignant ascites (MA) is most commonly observed in patients scheduled for epithelial ovarian cancer (EOC) surgery and is supposed as a major risk factor promoting perioperative hemodynamic deterioration. We aimed to assess the hemodynamic consequences of MA on systemic circulation in patients undergoing cytoreductive EOC surgery. This study is a predefined post-hoc analysis of a randomized controlled pilot trial comparing intravenous solutions within a goal-directed algorithm to optimize hemodynamic therapy in patients undergoing cytoreductive EOC surgery. Ascites was used to stratify the EOC patients prior to randomization in the main study. We analyzed 2 groups according to the amount of ascites (NLAS: none or low ascites [<500 mL] vs HAS: high ascites group [>500 mL]). Differences in hemodynamic variables with respect to time were analyzed using nonparametric analysis for longitudinal data and multivariate generalized estimating equation adjusting the analysis for the randomized study groups of the main study. A total of 31 patients in the NLAS and 16 patients in the HAS group were analyzed. Although cardiac output was not different between groups suggesting a similar circulatory blood flow, the HAS group revealed higher heart rates and lower stroke volumes during surgery. There were no differences in pressure-based hemodynamic variables. In the HAS group, fluid demands, reflected by the time to reindication of a fluid challenge after preload optimization, increased steadily, whereas stroke volume could not be maintained at baseline resulting in hemodynamic instability after 1.5 h of surgery. In contrast, in the NLAS group fluid demands were stable and stroke volume could be maintained during surgery. Clinically relevant associations of the type of fluid replacement with hemodynamic consequences were particularly observed in the HAS group, in which transfusion of fresh frozen plasma (FFP) was associated to an improved circulatory flow and reduced vasopressor and fluid demands, whereas the administration of artificial infusion solutions was related to opposite effects. Malignant ascites >500 mL implies increased fluid demands and substantial alterations in circulatory blood flow during cancer surgery. Fresh frozen plasma transfusion promotes recovering hemodynamic stability in patients with malignant ascites >500 mL, in whom artificial infusion solutions could not prevent from hemodynamic deterioration.